Legal Protection for T-Shirt Design Owners from the Perspective of the MUI Fatwa No. 1 MUNAS VII/MUI/5/2005 (A Study of the Shopee Marketplace) - Yusri, Lisa; Sativa, Annisa (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
In creating a clothing design, it takes a long process to obtain inspiration and careful consideration accompanied by research first. However, this time-consuming process causes many people to not appreciate the process of creating a clothing design. So many people decide to imitate other people's pre-existing designs. The violation of industrial design rights discussed by this author is that an unregistered mark imitates or plagiarizes a registered mark as determined in Article 54 of Law of the Republic of Indonesia Number 31 of 2000 concerning Industrial Design. In fact, this of course violates the copyright of the work created by the designer, where he does not get the commission rights that he should get. In this research, the author used a Normative research method, in legal research there are several statutory approaches which are carried out by examining the laws and regulations that are related to the issue at hand. The results of this research show that there is imitation of t-shirt designs in the market place shop. The imitation is in the same shape, image and lines. According to MUI Fatwa NUMBER 1 MUNAS VII/MUI/5/2005, protection for t-shirt designs is preventive or preventive in nature because violations of IPR are haram and according to the law will be subject to criminal or civil sanctions.